2020
DOI: 10.1007/s12540-020-00890-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conventional and Severe Shot Peening on Residual Stress and Fatigue Strength of Steel AISI 1060 and Residual Stress Relaxation Due to Fatigue Loading: Experimental and Numerical Simulation

Abstract: This study investigates and compares the effects of different shot peening treatments including conventional and severe shot peening on microstructure, mechanical properties, fatigue behavior, and residual stress relaxation of AISI 1060 steel. Shot peening treatments were applied with two Almen intensities of 17 and 21 A and a wide ranges of coverage (100%–1500%). Various microstructural observations were carried out to analyze the evolution of microstructure. Microhardness, residual stress and surface roughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 37 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…7, the FWHM values at the topmost surface for (110) lattice plane increase with coverage levels, and the value of SP40 increases by 32.16% compared with that of SP1. The grain size is negatively correlated with FWHM [52]. Hence, it is revealed that with the increase of coverage, grain size at the topmost surface decreases, whereas FWHM becomes wider.…”
Section: Phase Analysismentioning
confidence: 82%
“…7, the FWHM values at the topmost surface for (110) lattice plane increase with coverage levels, and the value of SP40 increases by 32.16% compared with that of SP1. The grain size is negatively correlated with FWHM [52]. Hence, it is revealed that with the increase of coverage, grain size at the topmost surface decreases, whereas FWHM becomes wider.…”
Section: Phase Analysismentioning
confidence: 82%
“…On the other hand, artificial intelligence (AI) based methods such as neural networks (NN) are remarkably applied in different aspects of science and engineering [26][27][28][29], as well as their applications in fatigue behavior prediction and analysis [30][31][32][33][34][35] and modelling of SP process [28,30,[36][37][38]. In general, a neural network has three major layers of input, hidden and output [39].…”
Section: Introductionmentioning
confidence: 99%
“…Surface strengthening by different severe plastic deformation (SPD) methods has been widely perceived to enhance surface mechanical properties [1]. Researchers have used SPD by shot peening [2,3], severe shot peening (SSP) [4,5], ultrasonic impact peening [6,7], ultrasonic shot peening (USP) [8,9], laser shock peening [10,11], direct and indirect laser shock surface patterning (LSSP) [12,13], surface mechanical attrition treatment (SMAT) [14,15], and deep cold rolling (DCR) [16]. These surface SPD techniques could induce residual compressive stress (RCS) and closure of existing microcracks and microcavities on the surface [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%